GLDC mitigated by miR-30e regulates cell proliferation and tumor immune infiltration in TNBC - Xie, Huaying; Yan, Tingting; Lu, Xinxin; Du, Yueyao; Xu, Shuguang; Kong, Yu; Yu, Liangjie; Sun, Jian; Zhou, Liheng; Ma, Jun (Frontiers in Immunology, 2022)
Background: TNBC, whose clinical prognosis is poorer than other subgroups of breast cancer, is a malignant tumor characterized by lack of estrogen receptors, progesterone hormone receptors, and HER2 overexpression. Due to the lack of the specific targeted drugs, it is crucial to identify the critical factors involved in regulating the progression of TNBC. Methods: We analyzed the expression profiles of TNBC in TCGA and the prognoses values of GLDC. The correlations of GLDC and tumor immune infiltration were also identified. CCK8 and BrdU incorporation assays were performed to determine cell proliferation. The mRNA and protein levels were examined by using Real-time PCR and Western blot analysis. Results: In the present study, we analyzed the mRNA expression profiles of TNBC in TCGA and found that GLDC, a key enzyme in glycine cleavage system, was significantly up-regulated in TNBC tissues and higher expression of GLDC was correlated with a worse prognosis in TNBC. Moreover, the expression of GLDC was negatively correlated with macrophage and monocyte and positively correlated with activated CD4 T cell and type 2 T helper cell in TNBC. Overexpression of GLDC facilitated the proliferation of TNBC cells, whereas GLDC knockdown had the opposite effects. Additionally, miR-30e acts as an upstream functional regulator of GLDC and the inhibitory effects of miR-30e on cell proliferation were mitigated by the reintroduction of GLDC. Conclusions: These results imply that miR-30e-depressed GLDC acts as a tumor suppressive pathway in TNBC and provides the potential targets for the treatment of TNBC.